ELIGIBILITY OF TIKTOK SHOP AS A LEGITIMATE PLATFORM FOR CONDUCTING ONLINE SALES TRANSACTIONS IN INDONESIA - Siswapranata, Fadiana Zahra; Mediawati, Noor Fatimah (Antis Publisher, 2024)
General Background: The rapid evolution of digital marketplaces has transformed the landscape of online sales, particularly in emerging markets like Indonesia. Specific Background: TikTok Shop, a relatively new platform developed by ByteDance, leverages the popularity of social media to facilitate online transactions. Despite its growing user base, limited research has been conducted on its legal and operational viability in the Indonesian market. Knowledge Gap: This gap highlights the need for a comprehensive analysis of TikTok Shop within the framework of Indonesian trade regulations, particularly Law Number 7 of 2014 concerning Trade. Aims: This research aims to evaluate the feasibility of TikTok Shop as a marketplace for online sales transactions in Indonesia, exploring its advantages and legal implications. Results: Through a Normative Juridical methodology, the study identifies key benefits of TikTok Shop, including its user-friendly interface, integration with social media marketing, and the potential for enhanced consumer engagement. Novelty: This research contributes to the literature by providing a focused examination of a novel marketplace platform and its alignment with existing legal frameworks in Indonesia. Implications: The findings suggest that TikTok Shop presents a viable option for online sales, promoting innovation in e-commerce while also necessitating careful consideration of regulatory compliance to ensure sustainable growth within Indonesia’s digital economy.